2019
DOI: 10.1158/0008-5472.can-18-2931
|View full text |Cite
|
Sign up to set email alerts
|

Asporin Restricts Mesenchymal Stromal Cell Differentiation, Alters the Tumor Microenvironment, and Drives Metastatic Progression

Abstract: Tumor progression to metastasis is not cancer cell autonomous, but rather involves the interplay of multiple cell types within the tumor microenvironment. Here we identify asporin (ASPN) as a novel, secreted mesenchymal stromal cell (MSC) factor in the tumor microenvironment that regulates metastatic development. MSCs expressed high levels of ASPN, which decreased following lineage differentiation. ASPN loss impaired MSC self-renewal and promoted terminal cell differentiation. Mechanistically, secreted ASPN bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 64 publications
(116 reference statements)
2
47
0
Order By: Relevance
“…MSCs have been isolated from different types of human malignancies, including head and neck (Kansy et al, 2014), glioma (Behnan et al, 2014;Hossain et al, 2015;Shahar et al, 2017;Svensson et al, 2017), breast metastasis (Gonzalez et al, 2017), cervical (Avila-Ibarra et al, 2019), ovarian (McLean et al, 2011;Coffman et al, 2019;Naour et al, 2019), lung (Galland et al, 2017), prostate (Hughes et al, 2019), neuroblastoma (Pelizzo et al, 2018), and colorectal (Zhang et al, 2018) cancer. Even if the MSCs in these studies adhered to the ISCT phenotype (Dominici et al, 2006), it is important to bear in mind that tumor cells can also exhibit a mesenchymal-like phenotype, making it difficult, or even impossible, to discriminate them from MSCs.…”
Section: Msc Phenotype and Originmentioning
confidence: 99%
“…MSCs have been isolated from different types of human malignancies, including head and neck (Kansy et al, 2014), glioma (Behnan et al, 2014;Hossain et al, 2015;Shahar et al, 2017;Svensson et al, 2017), breast metastasis (Gonzalez et al, 2017), cervical (Avila-Ibarra et al, 2019), ovarian (McLean et al, 2011;Coffman et al, 2019;Naour et al, 2019), lung (Galland et al, 2017), prostate (Hughes et al, 2019), neuroblastoma (Pelizzo et al, 2018), and colorectal (Zhang et al, 2018) cancer. Even if the MSCs in these studies adhered to the ISCT phenotype (Dominici et al, 2006), it is important to bear in mind that tumor cells can also exhibit a mesenchymal-like phenotype, making it difficult, or even impossible, to discriminate them from MSCs.…”
Section: Msc Phenotype and Originmentioning
confidence: 99%
“…For instance, reciprocal reprogramming of cancer stem cells (CSCs) and associated MSCs may promote tumor progression in gastric cancer ( Shamai et al, 2019 ). Similarly, asporin, a factor secreted by MSCs following cellular interactions within the tumor microenvironment, altered the tumor microenvironment and inhibited MSC differentiation to drive metastatic progression through CD49d/CD29 signaling ( Hughes et al, 2019 ). Moreover, Dabbah et al (2019) reported that microvesicles derived from BM MSCs of multiple myeloma patients increased the tumorigenicity of MM cells ( Hughes et al, 2019 ).…”
Section: Evidence Of Stromal Cell Programming By Tumor Microenvironmementioning
confidence: 99%
“…Similarly, asporin, a factor secreted by MSCs following cellular interactions within the tumor microenvironment, altered the tumor microenvironment and inhibited MSC differentiation to drive metastatic progression through CD49d/CD29 signaling ( Hughes et al, 2019 ). Moreover, Dabbah et al (2019) reported that microvesicles derived from BM MSCs of multiple myeloma patients increased the tumorigenicity of MM cells ( Hughes et al, 2019 ). In this study, CD49d and CD29 integrin overexpression in MM-MSC microvesicles were associated with patient staging and response to treatment.…”
Section: Evidence Of Stromal Cell Programming By Tumor Microenvironmementioning
confidence: 99%
“…Recently, Hughes and co-workers found that asporin could not only sustain the self-renewal capacity of the mesenchymal stromal cell but also restrict early mesenchymal stromal cell differentiation via inhibiting the BMP-4-induced signaling pathway (67). Furthermore, in asporin null mice, they also found that there are decreased tumor-associated mesenchymal stromal cells, fewer cancer stem cells, reduced tumor vasculature, and increased infiltrating CD8 + T cells in the prostate tumor allografts (67). All these results indicate that asporin is a critical regulator in the tumor microenvironment possibly by regulating different signaling pathways except for TGF-β, EGFR, and CD44 pathways, and we can get some clues from previous studies not associated with cancer.…”
Section: Future Potential Directions Of Asporin Mediated Signaling Pamentioning
confidence: 99%
“…All these results indicate that asporin is a critical regulator in the tumor microenvironment possibly by regulating different signaling pathways except for TGF-β, EGFR, and CD44 pathways, and we can get some clues from previous studies not associated with cancer. As a secreted extracellular protein, it has been demonstrated that asporin could interact with several ligands as well as with surface receptors, including BMP-2, BMP-4, FGF-2, WNT8, Nodal, IGF, and IGF1R (33, 6769). Whether asporin could interact with these proteins and regulate the corresponding signaling pathways in cancer needs to be investigated in the future.…”
Section: Future Potential Directions Of Asporin Mediated Signaling Pamentioning
confidence: 99%